Superior memorizers employ different neural networks for encoding and recall - Mallow, Johannes; Bernarding, Johannes; Luchtmann, Michael; Bethmann, Anja; Brechmann, André (Frontiers in Systems Neuroscience, 2015)
Superior memorizers often employ the method of loci (MoL) to memorize large amounts of information. The method of loci, known since ancient times, relies on a complex process where information to be memorized is bound to landmarks along mental routes in a previously memorized environment. However, fMRI data on groups of trained superior memorizer are rare. Based on the memorizing strategy reported by superior memorizers we developed a scheme of the processes successively employed during memorizing and recalling digits and relate these to brain activation that is specific for the encoding and recall period. In the examined superior memorizers several regions, suggested to be involved in mental navigation and digit-to-word processing, were specifically activated during encoding: bilateral early visual cortex, retrosplenial cortex, left parahippocampus, left visual cortex, and left superior parietal cortex. Although the scheme suggests that some steps during encoding and recall seem to be analog, none of the encoding areas were specifically activated during the recall. Instead, we found strong activation in left anterior superior temporal gyrus, which we relate to recalling the sequential order of the digits, and right motor cortex that may be related to reciting the digits.